1997
DOI: 10.1037/0278-6133.16.4.319
|View full text |Cite
|
Sign up to set email alerts
|

Linking symptom-specific physiological reactivity to pain severity in chronic low back pain patients: A test of mediation and moderation models.

Abstract: Symptom-specific reactivity to stress (lower paraspinal muscle reactivity) among chronic low back pain (CLBP) patients may exacerbate chronic pain. It was hypothesized that among CLBP patients (N = 107) only stress-induced lower paraspinal reactivity, and not reactivity in other indexes, would predict pain severity (PS), and that lower paraspinal reactivity would mediate or moderate links between depression and PS. Electromyogram readings from lower paraspinal and trapezius muscles, systolic and diastolic bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 24 publications
(49 reference statements)
5
24
0
Order By: Relevance
“…Results support this kind of multi-variable approach. Burns et al (1997) found that the significant but modest main effect between depressed mood and chronic pain severity was moderated by stress-induced lower paraspinal reactivity, such that the highest chronic pain was reported by chronic low back pain patients with high levels of depressed mood and who showed high levels of lower paraspinal reactivity. Patients with high depressed mood but who were not strong lower paraspinal muscle reactors reported pain comparable to patients with low depressed mood.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Results support this kind of multi-variable approach. Burns et al (1997) found that the significant but modest main effect between depressed mood and chronic pain severity was moderated by stress-induced lower paraspinal reactivity, such that the highest chronic pain was reported by chronic low back pain patients with high levels of depressed mood and who showed high levels of lower paraspinal reactivity. Patients with high depressed mood but who were not strong lower paraspinal muscle reactors reported pain comparable to patients with low depressed mood.…”
Section: Introductionmentioning
confidence: 96%
“…The procedure was adapted from Dimsdale et al (1988). The anger and sadness recall procedures elicit significant muscle tension, SBP, DBP and HR reactivity (Burns et al 1997;Burns 2006b). Moreover, findings tell that both anger and sadness recall interviews elicit self-reported valence and arousal in expected directions (Burns et al 2003;Neumann and Waldstein 2001).…”
Section: Emotion-induction Interviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…One reasonable possibility is that anger exacerbates pain by increasing physiological arousal (Burns, 1997;Cacioppo, Bernston, Klein, & Poehlmann, 1997). For example, Burns, Wiegner, Derleth, Kiselica and Pawl (1996) reported the results of a study that demonstrated anger-induced stress produced increased muscle tension, which in turn predicted a greater level of pain severity in chronic back pain patients. It was found that this effect was specific to anger; a measure of depression that was significantly correlated with pain was not associated with increased muscle reactivity.…”
Section: Anxietymentioning
confidence: 99%